2018
DOI: 10.1016/j.aap.2018.06.014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ‘smart’ financial incentives on driving behaviour of novice drivers

Abstract: Recent studies have demonstrated that financial incentives can improve driving behaviour but high-value incentives are unlikely to be cost-effective and attempts to amplify the impact of low-value incentives have so far proven disappointing. The present study provides experimental evidence to inform the design of 'smart' and potentially more cost-effective incentives for safe driving in novice drivers. Study participants (n = 78) were randomised to one of four financial incentives: high-value penalty; low-valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Pay-as-you-drive (PAYD) and pay-how-you-drive (PHYD) are different UBI schemes whose premiums are affected by how much a vehicle is driven or how well. Offering monetary rewards for safer driving behaviours has a positive effect on behaviours, as suggested by Greaves and Fifer (2011), Reagan et al (2013) and Mortimer et al (2018). In turn, safer driving is expected to result in a lower number of fatal and serious crashes.…”
Section: Insurance Telematics and Their Impact On Behaviourmentioning
confidence: 91%
“…Pay-as-you-drive (PAYD) and pay-how-you-drive (PHYD) are different UBI schemes whose premiums are affected by how much a vehicle is driven or how well. Offering monetary rewards for safer driving behaviours has a positive effect on behaviours, as suggested by Greaves and Fifer (2011), Reagan et al (2013) and Mortimer et al (2018). In turn, safer driving is expected to result in a lower number of fatal and serious crashes.…”
Section: Insurance Telematics and Their Impact On Behaviourmentioning
confidence: 91%
“…In addition to the prevention of gaming behavior, another reason for using the loss-framed incentive is that the loss-framed incentive is more likely to elicit behavior change than the gain-framed incentive because of people’s tendency to place a greater emphasis on losses than gains, as stated by the prospect theory [ 43 ]. In practice, previous studies have demonstrated a better effect of the loss-framed incentive on health outcomes than the gain-framed incentive in a variety of intervention domains, including mitigating smartphone overuse [ 23 ], promoting physical activity [ 35 ], and improving driving behavior [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another aspect of incentive design that should be considered is the delay between behavior occurrence and incentive delivery, with a shorter delay having shown greater effectiveness in eliciting behavior change [ 18 , 33 ]. Other potential contributors to the effectiveness of contingency management include incentive framing (eg, providing incentives for positive behaviors vs deducting expenses for negative behaviors) [ 23 , 26 , 34 , 35 ], incentive magnitude adjustments throughout the intervention [ 20 , 34 , 36 , 37 ], and incentive magnitude certainty (eg, fixed vs lottery incentives) [ 4 , 12 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…[4] Creative insurance policy could have an impact on safety in conjunction with its design. [7] This may also have a major impact. Pay-as-you-drive schemes (PAYD) and the pay-how-you-drive (PHYD) are covered in insurance plans focused on vehicle use (UBI) with potential upcoming versions on PAHYD [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the activities followed by many insurance firms, research conducted by several scholars shows that insurance companies could also be interested in road safety through insurance schemes such as Travel actions and insurance driver-based behaviour [7]- [9]. Pricing of driving incentives [10/12].…”
Section: Introductionmentioning
confidence: 99%